FEATURES OF THE PRESENCE OF CULTURAL VALUE IN CULTURAL SPACE - Sunatov Dilshod Hoshimovich (Western European Studies, 2025)
This article provides a detailed explanation of the philosophical representation of cultural space, the history of the genesis, evolution and development of the concept of "being", the content and essence of cultural being, the scientific and philosophical views of some foreign and Uzbek philosophers on the characteristics of cultural being, and the classifications of "being" as a phenomenon
Keywords: phenomenon; dasiyn; being; Cultural being